The Role of Problematic Types of Physics Questions in Directing the Reader to Creative Activity (The Peerian Journal, 2022)
When improving the content of school education in physics using the problem type, the article describes the psychological components of a student's cognitive activity, its namelessness, the need to know, the structure of mental abilities. Using the problematic type of questions in the lesson, the features, opportunities and tasks of directing a student to creative activity are widely covered.